Surface strengthening of stainless steels by nondestructive laser peening. (July 2021) - Wang, Pengjie; Cao, Qiang; Liu, Sheng; Peng, Qing
Graphical abstract: Highlights: Nondestructive laser peening by low-energy femtosecond lasers. Surface enhancement in both linear and nonlinear mechanical properties. Simultaneous mechanical reinforcement and high-quality surface. Pinning mechanism on dislocation motion to enhance lattice strength. Abstract: Laser peening is an advanced technology for surface engineering. However, the unintentional surface destruction due to melting degrades the quality and reduces the corrosion resistance. Here we have introduced the nondestructive laser peening using femtosecond lasers with ultrahigh pulse density and ultralow pulse energy by a combined approach of experiment, finite element analysis, and molecular dynamics simulations, taken stainless steel as a paradigm. A reinforcement of 33.6% was achieved on surface hardness of American National Standards Institute (ANSI) 301 stainless steel with the pulse energy of 0.375 μJ (fluence of 0.45 J cm −2 ) and pulse density of 2 × 10 8 mm −2, without penalty in surface roughness compared with conventional nanosecond laser peening. Two-temperature finite element analysis indicates the non-melting of the peening process. Molecular dynamic simulations reveal the pinning mechanism on dislocation movement by defect meshes generated during femtosecond laser peening process. Dislocation pinning, multiplication, and intertwining enhance both the linear and nonlinear mechanical properties, agreeing well with experiment. With the atomistic insights, our results imply promising applications of nondestructive laser peening on various surfaces.